ANALYSIS OF SURFACE TEMPERATURE IN SLIDING CONTACT WITH TWO FRACTAL SURFACES - LAI LianFeng; GAO ChengHui; HUANG JianMeng (Jixie qiangdu)
A three-dimensional sliding model of micro-scale was established between two rough surfaces exhibiting fractal behavior,and the thermo-mechanical coupling factor in the process of contact was considered. The surface temperature in sliding processes was analysed using the finite element analysis taking into account Ti-6Al-4V elastic-plastic properties with material failure. The transient surface temperature distribution of the rough surface was presented. The numerical results showed that the surface temperature in initial time rise sharply and then tend to be temporarily stable until a new contacted asperity coming into interaction. With the increase of friction slide distance the surface temperature was to present the state of fluctuating. The values of highest temperature at contact zones were different,while the highest temperature at contact zone was higher relative to the greater interface shear strength. Compared with the experimental data of the literatures,it was concluded that the rationality of the simulation,these results also deepened understanding the reason of the friction and wear.